IMPLEMENTASI MODEL PANEL VAR PADA HUBUNGAN INFLASI DAN PERTUMBUHAN JUMLAH UANG BEREDAR: Studi Kasus 6 Negara ASEAN Tahun 1994-2020 - Pardomuan Robinson Sihombing; Ade Marsinta Arsani; Artha Satwika; Abdul Gofur Rochman (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2022)
This study aims to determine the causality relationship between the growth of the money supply (JUB) and inflation. The data used is panel data from 6 ASEAN countries in the 2009-2020 period. The analysis used is the Panel Vector Auto Regression (PVAR) model. The results showed a two-way causality relationship between the inflation rate and the growth of the money supply. The increase in inflation will reduce the growth of the money supply. Conversely an increase in the money supply will increase inflation. The government should keep these two macro variables balanced through existing fiscal and monetary instruments, for example with interest rate policy and price control, especially related to the price of staples and fuel